Equilibrium Relative Humidity-Equilibrium Moisture Content Isotherms of Oil Palm Kernels - Ibrahim, Mohamad Hakimi; Wan Daud, Wan Ramli; Ismail, Mohd Shihabuddin; Meor Talib, Meor Zainal (Universiti Putra Malaysia Press, 1997)
Equilibrium relative humidity-equilibrium moisture content (ERH-EMC) or moisture isotherms of solids is important in the drying, solid mixing, packaging and storage of such material. ERH-EMC isotherms of oil palm kernels are determined by using a constant environmental chamber for several combination of air relative humidity (30-90%) and temperature (30-70°C). The isotherms are found to fit the Hasley and Henderson equations well.